2017
DOI: 10.1111/tid.12786
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in the setting of renal transplantation: Case report and review of the literature

Abstract: The potent immunosuppressive drugs used by transplant recipients place them at risk of infections. Data on infective endocarditis (IE) in the setting of renal transplantation (RT) are sparse. We describe a 36-year-old woman referred to a tertiary medical center for evaluation of elevated creatinine levels 1 month after a second RT. Work-up revealed the presence of all four of Duke's criteria: fever, persistent bacteremia, new-onset tricuspid regurgitation, and masses suspected to be vegetation attached to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In that respect, the epidemiology in our study is closer to that of the general population [1]. We found that digestive bacteria predominate, with Enterococci as the most frequent pathogen, as previously described in SOTRs [14][15][16][17][18][19][20][21]. A hypothetical mechanism, in the absence of an identified digestive gateway (colonoscopy was performed in most of the cases where a digestive bacterium was identified, even though we did not collect the results of this exam in our study), could be the alteration of the gut microbiota by the combination of antibiotic treatments frequently used after transplantation, and of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In that respect, the epidemiology in our study is closer to that of the general population [1]. We found that digestive bacteria predominate, with Enterococci as the most frequent pathogen, as previously described in SOTRs [14][15][16][17][18][19][20][21]. A hypothetical mechanism, in the absence of an identified digestive gateway (colonoscopy was performed in most of the cases where a digestive bacterium was identified, even though we did not collect the results of this exam in our study), could be the alteration of the gut microbiota by the combination of antibiotic treatments frequently used after transplantation, and of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 83%
“…IE in KTRs occurred mostly in younger people than in the general population [ 1 , 6 , 7 , 11 ], and on hearts without any IE-predisposing conditions, as in the general population [ 14 ]. In our series, IE only occurred on left heart valves, but right heart valve IE has also been reported in KTRs previously [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In that respect the epidemiology in our study is closer to that of the general population [1]. We found that digestive bacteria predominate, with Enterococci as the most frequent pathogen as previously described in SOTRs [15][16][17][18][19][20][21]14,21]. A hypothetical mechanism, in the absence of an identified digestive gateway (colonoscopy was performed in most of the cases where a digestive bacterium was identified, even though we did not collect the results of this exam in our study), could be the alteration of the gut microbiota by the combination of antibiotic treatment frequently used after transplantation, and of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 76%
“…1,2 In a literature review of endocarditis in renal transplant patients, 73 cases were detected, and while indeed S aureus was the most common pathogen, Enterococcus was found to cause the same number of infections (N = 13 [18%]). 13 IE attributable to mold has been well-described in previous reports of IE in SOT patients. 1,2 In a review of SOT patients with IE prior to 1998, fungi caused infection in 28%, and most were disseminated mold.…”
Section: Re Sultsmentioning
confidence: 60%
“…Regarding the microbiologic diagnosis, it has been shown that S aureus is most commonly identified as the etiologic agent in IE in the modern era, 10‐12 including in SOT patients 1,2 . In a literature review of endocarditis in renal transplant patients, 73 cases were detected, and while indeed S aureus was the most common pathogen, Enterococcus was found to cause the same number of infections (N = 13 [18%]) 13 1,2 .…”
Section: Discussionmentioning
confidence: 99%